New polymorph of tofacitinib citrate and in vitro equivalence study of its sustained-release tablets - Yan Wang; Shuai Wen; Yao Zhao; Lijuan Gui; Yi Mou; Dongkai Wang (PLoS ONE, 2025)
Tofacitinib citrate (TOC) is clinically used primarily for the treatment of moderate to severe rheumatoid arthritis in patients who are intolerant or inadequately responsive to methotrexate. In this study, a new polymorph of TOC (form II) was prepared using solvent crystallization. The currently marketed form I and the self-prepared form II were characterized by XRD, DSC, FT-IR, and SEM, confirming that form II is a new polymorphic form of TOC. This new polymorph was then used in the development of TOC sustained-release tablets. In the formulation design, mannitol with low hygroscopicity was used to replace sorbitol. By adding a certain amount of microcrystalline cellulose to the tablet core and maintaining the mannitol content between 60 ~ 70% of the total core weight, an in vitro dissolution behavior similar to that of the reference formulation (f2 > 50) was achieved. This indicates that replacing sorbitol with mannitol as the osmotic agent in the osmotic pump tablet core is a practical and effective method. Additionally, key preparation processes for the TOC sustained-release tablets were investigated. The results suggest that the coating weight gain of the self-prepared sustained-release tablets should be controlled between 6% and 7%, and the suitable range for laser-drilled orifice diameter is 0.55 ~ 0.90 mm.